1994
DOI: 10.1177/107110079401500901
|View full text |Cite
|
Sign up to set email alerts
|

Distal Chevron Osteotomy with Lateral Release for Treatment of Hallux Valgus Deformity

Abstract: From 1986 to 1990, 42 feet in 30 patients had a combined chevron osteotomy and lateral release to correct their painful bunion deformity. Seventeen patients, 23 feet, were available for follow-up. The purpose of this study was to evaluate the outcome of this procedure and to determine the incidence of avascular necrosis. The patients were examined by an independent examiner, radiographs obtained, and questionnaires filled out. Avascular necrosis was determined using plain films read by a musculoskeletal radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
8

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 15 publications
6
60
0
8
Order By: Relevance
“…En nuestra práctica solamente la aplicaremos, como defiende Schnepp 32 , cuando comprobemos que una osteotomía distal no nos ha dado la corrección necesaria del mismo, y por tanto realizamos la osteotomía bipolar (distal y proximal) que haremos por técnicas percutáneas 33 obteniendo resultados muy satisfactorios. La corrección obtenida sobre el ángulo metatarsofalángico con la práctica de osteotomías distales del primer metatarsiano es limitada, aproximadamente entre 10 a 25°según las series 34,35 ; por esta razón, diversos autores 6,25,[36][37][38] recomiendan asociar la liberación de la cápsula lateral y desinserción del abductor a nivel de la falange, con lo que se consiguen correcciones muy superiores a los 25°.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En nuestra práctica solamente la aplicaremos, como defiende Schnepp 32 , cuando comprobemos que una osteotomía distal no nos ha dado la corrección necesaria del mismo, y por tanto realizamos la osteotomía bipolar (distal y proximal) que haremos por técnicas percutáneas 33 obteniendo resultados muy satisfactorios. La corrección obtenida sobre el ángulo metatarsofalángico con la práctica de osteotomías distales del primer metatarsiano es limitada, aproximadamente entre 10 a 25°según las series 34,35 ; por esta razón, diversos autores 6,25,[36][37][38] recomiendan asociar la liberación de la cápsula lateral y desinserción del abductor a nivel de la falange, con lo que se consiguen correcciones muy superiores a los 25°.…”
Section: Discussionunclassified
“…Estos datos están en absoluta discordancia con los aportados por otros autores 6,38 en los que no se aprecia aumento de necrosis vascular de la cabeza metatarsiana tras osteotomía con liberación lateral de partes blandas. Esto nos hace pensar que esos resultados tan negativos están directamente relacionados con la vía de abordaje que los autores precedentes utilizaban, y que si la realizamos de una manera adecuada, como proponen Jones et al 43 , los resultados son totalmente superponibles a las series en las que no se hace liberación de las partes blandas.…”
Section: Discussionunclassified
“…Steinböck [26] was the first to routinely combine the Austin osteotomy with a distal soft tissue procedure without increased risk of osteonecrosis of the metatarsal head. Anatomical studies [9] have confirmed the possibility of a safe combination of distal metatarsal osteotomy with lateral release, provided that the osteotomy is performed in a "safe zone", followed by clinical studies confirming the risk free combination of soft tissue procedure and osteotomy [5,7,[27][28][29][30]. Additionally, the blood supply into the metatarsal head via plantar and dorsal capsular attachment should be left intact.…”
Section: Medial Capsular Repairmentioning
confidence: 99%
“…This soft tissue procedure aims to restore the physiological balance of capsular, ligamentous and muscular structures around the first metatarsophalangeal (MTP) joint. During the last decades worldwide scientific discussions, clinical surveys [1][2][3][4][5][6][7][8], anatomical studies [9,10] and experimental set-ups [11][12][13][14] have helped to clarify open questions about soft tissue procedures: is it necessary in every case of bunion surgery and is there a technique superior in respect of high efficiency and low risk? Certain reservations exist regarding the combination of distal soft tissue procedures and distal metatarsal osteotomies.…”
Section: Introductionmentioning
confidence: 99%
“…No evidence of avascular of the metatarsal head was recorded in this series. Other studies did not report that also after Chevron osteotomy [8,11,18,27,40,43,54] . Some studies reported that patients underwent for corrective surgery for hallux valgus are at a low risk for venous thrombosis following the surgical procedure [42] .…”
Section: Discussionmentioning
confidence: 99%